The madrasah principal’s strategies to maximize teaching and learning processes during the covid-19 pandemic - Syaiful Bahri (Indonesian Institute for Counseling, Education and Therapy (IICET), 2022)
The Madrasah principal's strategy is the most decisive factor in the success of maximizing teaching and learning processes at Madrasah. This research was motivated by the difficulties of Madrasah Jauharussa'adah in carrying out learning processes during the Covid-19 pandemic to describe the Madrasah principal’s strategies to maximize teaching and learning process during such. This research adopted a qualitative approach. The consideration of taking this research object was because the researcher wanted to reveal that not a few educational units were confused in carrying out learning processes during the pandemic COVID-19. Meanwhile, the object under study was in the countryside. Data collection processes were carried out by interviews, observations, and documentations. The subjects of this study were the Madrasah principal and the teacher council. The data were analyzed by means of data reduction, data presentation, and conclusion drawing. The findings showed that the first Madrasah principal’s strategy to maximize teaching and learning processes at Madrasah Jauharussa'adah during the covid-19 pandemic was using a module system. The second strategy was the application of a small-group technique. The module system was implemented in a face-to-face mode. The duration of learning was set to only took 25 minutes.